Evaluation of Cardiovascular Toxicity Associated with Treatments Containing Proteasome Inhibitors in Multiple Myeloma Therapy - Iannaccone, Andrea; Bruno, G.; Ravera, A.; Gay, F.; Salvini, M.; Bringhen, S.; Sabia, L.; Avenatti, E.; Veglio, F.; Milan, A. (High blood pressure & cardiovascular prevention, 2018)
Introduction Recently new treatment options have substantially increased survival for patients with relapsed and/or refractory multiple myeloma (RRMM). Among these, proteasome inhibitors (PI), such as bortezomib and carfilzomib, offer high response rate and prolonged survival. These agents are generally well tolerated but demonstrated a significant cardiovascular toxicity, mostly for regimen containing carfilzomib. Aim To assess the cardiovascular damage in patients treated with PI for RRMM. Methods 28 consecutive subjects treated with PI for RRMM were evaluated and compared with a population of 22 control (Con) subjects, matched for age, sex and mean 24 h blood pressure (24hMBP). All individuals underwent trans-thoracic echocardiography, ambulatory blood pressure monitoring and pulse wave velocity (PVW) study. Results PI patients did not have significant differences in blood pressure load and PWV compared to controls. Among echocardiographic parameters, the global longitudinal strain (GLS) was significantly decreased in PI subjects (p = 0.02). The GLS was significantly lower also considering only patients treated with carfilzomib. Moreover, among carfilzomib patients, we found increase values of left ventricle mass indexed by BSA (LVMi; p = 0.047). After correction for age, sex, BSA, 24hMBP and morphological and functional parameters of LV, treatment with PI and carfilzomib were significantly associated with GLS (p = 0.01; p = 0.036, respectively). Conclusions PI treatment is associated with subclinical LV dysfunction in patients with RRMM compared to controls, as demonstrated by lower GLS values. These results are confirmed also considering patients treated with carfilzomib. Moreover, in this subgroup of patients, the LVMi is also increased, suggesting higher cardiotoxicity with this treatment.